Unified code-compliant equations for bending and ductility capacity of full and hollow rectangular RC sections. (15th March 2019) - Petrone, Floriana; Monti, Giorgio
Highlights: Code-compliant closed-form equations for yield/ultimate capacity of full/hollow rectangular RC sections are presented. The equations are fully parameterized to model a variety of cross-sections with steel on four sides. The equations provide an efficient tool for performing parametric or stochstic massive analyses. The equations can be used for rapid assessment of existing territorially-distributed systems according to any Codes. The accuracy of the proposed is demonstrated through comparison with fiber-section analyses. Abstract: Simple closed-form code-compliant equations for determining the bending capacity of full and hollow rectangular reinforced concrete (RC) sections at yielding and ultimate are proposed. The equations, based on the material models of ACI 318-14 and EN 1992:2005, are fully parameterized and allow modeling square and rectangular cross-sections with steel arbitrarily distributed on all four sides and subjected to axial force and uniaxial bending moment. Because of their simplicity, the equations provide an efficient tool for performing parametric and stochastic massive analyses, and for rapidly assessing existing territorially-distributed infrastructural systems, such as highways and railways. The equations require the definition of the cross-sections material and geometrical properties and are of general validity, since any geometrical configurations, reinforcement arrangements and concrete constitutive models can be employed. The accuracy of the equations in predicting bending capacity (resisting moment), ductility and axial force-bending moment interaction domain of a representative sample of realistic full and hollow RC sections is demonstrated through comparisons with fiber analysis performed in OpenSees.